Changes of Physical Activity and Ultra-Processed Food Consumption in College students during COVID-19 Pandemic: An Observational Study: PERUBAHAN AKTIVITAS FISIK DAN KONSUMSI MAKANAN ULTRA PROSES PADA MAHASISWA SELAMA PANDEMI COVID-19: PENELITIAN OBSERVASIONAL - Ratih Wirapuspita Wisnuwardani; Reny Noviasty; Amanda Saputri; Eva Rully Kurniawati (Media Gizi Indonesia, 2022)
The government has developed initiatives to restrictive activity during the COVID-19 pandemic, which have led to changes in lifestyle habits, especially those involving physical activity and food consumption. Changes of physical activity and ultra-processed foods consumption have occurred in several countries during the COVID-19 pandemic. The changing of lifestyle might affect obesity that 32.5% of the population (>18 years) in Samarinda, East Kalimantan, Indonesia are obese. Good eating behaviours in the early stages of life and adolescence can influence the current health status and the predisposition to non-communicable diseases in adulthood. Therefore, this cross-sectional study with 378 college students aimed to determine changes of physical activity and ultra-processed foods consumption in college students during restrictive activity in the COVID-19 pandemic. Data was collected using an online questionnaire for two months. Further, data was analyzed using Wilcoxon and chi-square test with 95% confidence level (α= 0.05). This study showed that the prevalence of normal nutritional status was 60.1%, inactive physical activity status was 89.4%, and the consumption level of ultra-low processed foods was 82.5%. Statistical tests obtained p-value differences in physical activity (p=<0.001) and differences in ultra-processed food consumption (p=0.034) before and after the restrictive activity in the COVID-19 pandemic. Additionally, mother's educational level (p=0.004) and the number of occupants in the house (p=0.001) significantly affected the consumption of ultra-processed  foods.